How household chaos affects social withdrawal of rural children: the indirect role of executive function and receptive language ability - Zhan, Shuwei; Guo, Jinna (Frontiers in Psychology, 2023)
Executive function (EF) and receptive language ability play an important role in the relationship between household chaos and social withdrawal. Young children are neglected in household chaos research and suffer from the negative outcomes of households in China. However, few studies have focused on the relationship between household chaos and social withdrawal in young Chinese children and the chain mediating effect of EF and receptive language ability. This study included 922 preschool-age children (62.58 ± 8.03 months) and their primary caregivers and their teachers were recruited from 21 rural preschools in Guangdong Province in China. Our results show a positive direct effect of household chaos and social withdrawal. Furthermore, an indirect sequential effect of household chaos and social withdrawal on EF and receptive language ability was found. Our findings (a) highlight the significance of paying more attention to household chaos and revealing a better understanding of the effect of EF and receptive language ability on households at an early age and (b) indicate that interventions should be provided to improve the home environment when children are young.